Financial Management Strategy in the General Election Supervisory Agency in Achieving the Sustainable Development Goals (SDG): A Review of Budget Performance and Use - Habibullah, Habibullah; Marantika, Abshor; Kasmawati, Kasmawati (Dinasti Publisher, 2026)
Management efficient finance​ is base important for institution government for reach optimal performance, especially in supervision ongoing elections​ changed. Research This analyzing management strategies finance at the Supervisory Agency Election General Elections Supervisory Agency (Bawaslu) of Riau Province, with emphasis on performance organization and efficiency use budget. With approach qualitative descriptive, data obtained through analysis document budget annual (2019-2023), interview deep with 15 officials key, and observation to the budgeting process. Findings study show that management strategy finance Bawaslu Riau still relies heavily on allocations from center, with an average absorption budget by 85% and efficiency performance reached 78% based on KPI indicators. However, there are inefficiency in management risk finance and adjustments to change regulations, which resulted in waste up to 15% of the total budget. Implications from study This includes suggestions for strengthen data - driven planning and integration technology finance, which can increase accountability as well as sustainability institution supervisor elections at the level province. Research This give contribution to the literature about management finance public in Indonesia, with focus on context democracy at the regional level.